Distal Renal Tubular Acidosis Presenting As Hypokalemic Periodic Paralysis - Amitabh Ranjan; Pradeep Debata (Asian Journal of Clinical Pediatrics and Neonatology, 2013)
We report a 4 year old child with periodic paralysis secondary to distal renal tubular acidosis. Although, hypokalemia with muscle weakness is associated with distal renal tubular acidosis, hypokalemic periodic paralysis without typical features, is very uncommon. The patient responded well both, clinically and biochemically, to alkali and potassium supplements.